Analisis Aspek Pedagogis Kontemporer Berdasarkan Implikatur dalam Puisi-puisi Asy-Syafi'i - Pamungkas, Muhammad Ibnu; Syihabuddin, Syihabuddin (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2025)
The poems of Asy-Syafi'i, rich in linguistic artistry and profound moral messages, contain implicit meanings that reflect essential pedagogical values. Understanding the implicatures in these poems provides deeper insights into the educational messages conveyed indirectly. This study examines the contemporary pedagogical aspects embedded in the poems of Asy-Syafi'i. The purpose of this research is to analyze these implicit contemporary pedagogical messages using implicature theory, offering deeper insights into how Asy-Syafi'i’s poems promote moral, spiritual, and intellectual development. The methodology used is a descriptive qualitative approach with a pragmatic framework. The study involves text analysis and a literature review to identify the implicatures within the poems. This approach allows for a comprehensive understanding of the underlying contemporary pedagogical values that are often subtly conveyed. The results of the analysis reveal that Asy-Syafi'i’s poems emphasize the importance of manners, dedication, and moral purity in the pursuit of knowledge. The implications of this research suggest that by exploring the implicatures in Asy-Syafi'i’s poetry, readers can gain a deeper understanding of Islamic contemporary pedagogical values. These findings contribute to the broader field of Islamic literature and education by highlighting how literary works effectively transmit values that shape personal development and educational practices.